Optimalisasi Alur Pelayanan Vaksinasi Covid-19 di RSU X Kota Bandung Tahun 2021 - Yola Nikmatillahi; Sali Setiatin; Ihsan Marga Wiyaksa (Jurnal Health Sains, 2021)
The number of patients infected with positive cases of Corona Virus Disease 2019 (COVID-19) in Indonesia is increasing. COVID-19 was previously known as Novel 201 Novel Coronavirus (2019-nCoV) a disease that affects the respiratory system. In an effort to reduce the number of positive cases of the corona virus, the government urges all Indonesians to vaccinate against COVID-19, as an effort to prevent the spread of the COVID-19 virus. The provision of COVID-19 vaccination is carried out through government or private health service facilities that have been appointed and have met the standards. The purpose of this study was to analyze the flow of COVID-19 vaccination services at RSU X Bandung City. The research method used is a qualitative method with a descriptive approach, data collection techniques using observation and literature study. The results of this study are the flow of COVID-19 vaccination services at RSU X Bandung City is simplified into the second rule set by the Ministry of Health of the Republic of Indonesia. The simplification of the COVID-19 vaccination flow is expected to facilitate targets and speed up the process of vaccination services. However, the results were not optimal in providing COVID-19 vaccination services. There are several obstacles such as the length of time for screening, data entry, ineffective space and time provisions, causing queues for vaccine recipients and service support facilities